THE EFFECT OF TWO STAY TWO STRAY STRATEGY ON READING COMPREHENSION ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 KANDIS - Nurul Ainain; Dahnilsyah Dahnilsyah; M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This Pre-experimental research aims to find out whether or not there is a significant effect of using Two Stay Two Stay Strategy on reading comprehension ability of the second year students of SMAN 1 Kandis. The sample of this research is 35 students of XI IPA 1 chosen by cluster random sampling. To measure the students’ reading comprehension level, pre-test and post-test in form of recount text are given before and after treatment. The results of the data analysis show that the mean score of the pre-test is 52.27 and the mean score of post-test is 79.92. It means the mean score of post-test is higher than pre-test. In addition, the value of t-obs is higher than t-table (11.66>2.03). Therefore, it can be concluded that there is a significant effect of Two Stay Two Stray Strategy on reading comprehension of the second year students of SMAN 1 Kandis.Key Words: Effect, Two Stay Two Stray Strategy, Reading Comprehension, Recount Text.